Genetics and Molecular Mapping of Heat Tolerance for Seedling Survival and Pod Set in Lentil. Issue 6 (28th September 2017) - Singh, Dharmendra; Singh, Chandan Kumar; Singh Tomar, Ram Sewak; Pal, Madan
Abstract : Heat stress is one of the most severe abiotic stresses affecting yield of agricultural crops. Its effects can be minimized through development of heat‐tolerant genotypes. In this study, the populations were developed through crossing heat‐stress‐sensitive ('JL‐3' and E‐153) and tolerant (PDL‐1 and PDL‐2) lentil ( Lens culinaris Medik.) genotypes for studying the genetics and molecular mapping of heat tolerance. The parents, F1, F2, F3, and backcross populations were exposed to heat stress at seedling (35/33°C) and reproductive (35/20°C) stages under hydroponic assay. The F1 s were found tolerant, indicating dominance of heat tolerance based on seedling survival and pod set per plant. The segregation ratios obtained for heat tolerance in the F2, F3, and backcross populations were 3:1, 1:2:1, and 1:1 based on seedling survival and pod set per plant. This suggested the presence of a single dominant gene for seedling survival and pod set related to heat tolerance in PDL‐1 and PDL‐2. This matched with one major quantitative trait locus (QTL) in each trait (i.e., seedling survival and pod set per plant). Out of 495 simple sequence repeat markers used in this study, 13 distinguished the parental lines. However, tolerant and sensitive bulks could be distinguished by seven markers, which were used for genotyping the F2 mapping population. The QTL analysis using data for genotyping and phenotyping identified two major QTLs, qHt_ss and qHt_ps, with 12.1 and 9.23% phenotypic variance explained for seedling survival and pod set, respectively. These QTLs would provide further opportunities to dissect candidate genes and development of molecular markers for improving lentil cultivars with heat tolerance.